MAF1 suppresses AKT‐mTOR signaling and liver cancer through activation of PTEN transcription. Issue 6 (31st March 2016) - Li, Yue; Tsang, Chi Kwan; Wang, Suihai; Li, Xiao‐Xing; Yang, Yang; Fu, Liwu; Huang, Wenlin; Li, Ming; Wang, Hui‐Yun; Zheng, X.F. Steven
Abstract : The phosphatidylinositol 3‐kinase/phosphatidylinositol 3, 4, 5‐trisphosphate 3‐phosphatase/protein kinase B/mammalian target of rapamycin (PI3K‐PTEN‐AKT‐mTOR) pathway is a central controller of cell growth and a key driver for human cancer. MAF1 is an mTOR downstream effector and transcriptional repressor of ribosomal and transfer RNA genes. MAF1 expression is markedly reduced in hepatocellular carcinomas, which is correlated with disease progression and poor prognosis. Consistently, MAF1 displays tumor‐suppressor activity toward in vitro and in vivo cancer models. Surprisingly, blocking the synthesis of ribosomal and transfer RNAs is insufficient to account for MAF1's tumor‐suppressor function. Instead, MAF1 down‐regulation paradoxically leads to activation of AKT‐mTOR signaling, which is mediated by decreased PTEN expression. MAF1 binds to the PTEN promoter, enhancing PTEN promoter acetylation and activity. Conclusion : In contrast to its canonical function as a transcriptional repressor, MAF1 can also act as a transcriptional activator for PTEN, which is important for MAF1's tumor‐suppressor function. These results have implications in disease staging, prognostic prediction, and AKT‐mTOR‐targeted therapy in liver cancer. (Hepatology 2016;63:1928‐1942)